Leptin favors Th17/Treg cell subsets imbalance associated with allergic asthma severity. Issue 6 (14th June 2022) - Vollmer, Carolina M.; Dias, Aleida S. O.; Lopes, Lana M.; Kasahara, Taissa M.; Delphim, Letícia; Silva, Júlio Cesar C.; Lourenço, Lucas Paulo; Gonçalves, Hilary Cesário; Linhares, Ulisses C.; Gupta, Sudhir; Bento, Cleonice A. M.
Abstract: Background: Obesity has often been associated with severe allergic asthma (AA). Here, we analyzed the frequency of different circulating CD4 + T‐cell subsets from lean, overweight and obese AA patients. Methods: Mononuclear cells from peripheral blood were obtained from 60 AA patients and the frequency of different CD4 + T‐cell subsets and type 1 regulatory B cells (Br1) was determined by cytometry. The effect of obese‐related leptin dose on cytokine production and Treg cell function in AA‐derived CD4 + T cell cultures was evaluated by ELISA and 3H thymidine uptake, respectively. Leptin levels were quantified in the plasma by ELISA. According to the BMI, patients were stratified as lean, overweight and obese. Results: AA severity, mainly among obese patients, was associated with an expansion of hybrid Th2/Th17 and Th17‐like cells rather than classic Th2‐like cells. On the other hand, the frequencies of Th1‐like, Br1 cells and regulatory CD4 + T‐cell subsets were lower in patients with severe AA. While percentages of the hybrid Th2/Th17 phenotype and Th17‐like cells positively correlated with leptin levels, the frequencies of regulatory CD4 + T‐cell subsets and Br1 cells negatively correlated with this adipokine. Interestingly, the obesity‐related leptin dose not only elevated Th2 and Th17 cytokine levels, but also directly reduced the Treg function in CD4 + T cell cultures from lean AA patients. Conclusion: In summary, our results indicated that obesity might increase AA severity by favoring the expansion of Th17‐like and Th2/Th17 cells and decreasing regulatory CD4 + T cell subsets, being adverse effects probably mediated by leptin overproduction.